The combined therapy of chronic hepatitis with pegilated interferon a-2а and ribavirin in patients with HIV-infection and patients with HCV monoinfection - N. D. Yuschuk; S. L. Maximov; L. M. Ivanova; Ye. K. Klimova; O. O. Znoyko; A. V. Kravchenko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. Studying of efficacy and safety of the combined therapy of chronic hepatitis C (CHC) by pegilated interferon α-2а in combination to ribavirin at early stages of chronic hepatitis and HIV-infection at patients receiving no high activity antiretroviral therapy (HAART), and comparison of these data with results of treatment of patients with HCV monoinfection.Materials and methods. Overall 50 CHC patients with HIV-infection at subclinical stage (stage 3–47 patients) and stage 4А of secondary diseases in remission phase without HAART (3 patients), as well as 49 CHC patients without HIV-infection – the 1st and 2nd groups respectively, were enrolled to the study. Pegilated interferon α-2а and ribavirin were prescribed to patients according to body weight for 48 wks irrespective to virus C genotype at combined HIV/CHC infection and for 24–48 wk in relation to virus C genotype – to CHC patients. The study had open, non-randomized, retrospective and prospective design.Results. The rate of achievement of sustained virologic response as a result of therapy of CHC at the HIVinfected patients is comparable to that for CHC patients without HIV-infection. Tolerability of combined therapy was satisfactory at the majority of patients. The most common adverse laboratory manifestations were thrombocytopenia, leukopenia and neutropenia which did not require cessation of treatment. Ten patients of 1st group (20%) dropped from the study, including 6 (12%) patients that were excluded because of development of side effects. The basic causes for cessation of therapy were depression and long-term fever. During treatment significant decrease of CD4+ lymphocyte number took place, however no clinical signs of HIV-infection progression has been found.Conclusions. Antiviral therapy at combined HIV/CHC infection should be prescribed to all patients from the moment of establishment of diagnosis of chronic hepatitis while patients require no HAART. It is recommended to carry out treatment of CHC at HIV-infected patients by pegilated interferon a-2а in combination to ribavirin which dose should be adjusted to body weight of the patient.